2015
DOI: 10.1080/09291016.2015.1073888
|View full text |Cite
|
Sign up to set email alerts
|

Effect of time of day on soccer specific skills in children: psychological and physiological responses

Abstract: The aim of the present study was to examine the effect of time-of-day on soccer specific skills and physiological and psychological parameters in children. Ten male children soccer players (age: 14.6 ± 0.8 years; height: 1.63± 0.4 m; body-mass: 52.5 ± 4.9 kg) performed two shooting accuracy tests before and after a 10 × 20-m dribbling sprint test with 20-s of passive recovery between repetitions. The measurements were taken at 08:00h, 13:00h and 17:00h in a randomized order. Mean heart rate (HR) was monitored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 19 publications
0
26
0
3
Order By: Relevance
“…One possible limitation for the present study was that the time of day of measurement was not taken into account. As previous studies have reported that physical and cognitive performance of children is dependent on time-of-day [39][40][41][42][43], further studies are needed to assess the physical fitness at the same daytime and during the same season.…”
Section: Discussionmentioning
confidence: 99%
“…One possible limitation for the present study was that the time of day of measurement was not taken into account. As previous studies have reported that physical and cognitive performance of children is dependent on time-of-day [39][40][41][42][43], further studies are needed to assess the physical fitness at the same daytime and during the same season.…”
Section: Discussionmentioning
confidence: 99%
“…In highly technical sports, evidence suggests that there could be a trade-off between timing of peak cognitive physical abilities, such that measures of accuracy (i.e. in dart-throwing or soccer goal aim) may be greater earlier in the day compared with the typical evening peak in meausres of more purely physical attributes like strength, speed, and endurance [11,12]. Although it can be difficult to distinguish between the many complex and intertwined factors that influence exercise performance, morning-evening differences in swim performance are at least partly attributable to the body's internal circadian clock [13].…”
Section: Exercise Performance and Training Efficacy Across The Daymentioning
confidence: 99%
“…La variable PSE ha sido eficazmente correlacionada con variables fisiológicas como la frecuencia cardíaca, lactato en sangre y desempeño técnico-táctico, 30,41,19 entre otras. La relación entre POMS y PSE en fútbol, son escasas.…”
Section: Discussionunclassified
“…Con respecto a la evaluación del estado emocional del deportista, se ha llevado a cabo mediante distintos instrumentos: Zonas Óptimas de Rendimiento Individuales emocionales (IZOF) 10 , Inventario de Ansiedad Rasgo-Estado (STAI) 11 , Inventario de Ansiedad Competitiva en el Deporte (CSAI-2) 12 , Escala de Ansiedad Deportiva (SAS) 13 , Inventario de Estado-Rasgo de Expresión de la Ira (STAXI-2) 14 y Perfil de Estados de Ánimo (POMS) 15,16 . El POMS ha sido ampliamente utilizado en fútbol 17,18,19,20 . En su forma original, estaba formado por una lista de 65 adjetivos que forman la prueba y representaban el resultado de un trabajo de repetidos análisis factoriales realizados con un total de 100 diferentes escalas de adjetivos 15 .…”
Section: Introductionunclassified
See 1 more Smart Citation